Metodo facil y confiable para teñir nucleos en hongos del complejo Rhizoctonia - Cedeño, L.
(Es, En)
Ilus., 17 ref.
Keywords: RHIZOCTONIA; MICOLOGIA; MICELIO; PAPA; VENEZUELA; TINCION; MORFOLOGIA HIFAL; BIOAGRO